EVALUATION OF RISK FACTORS IN PROGRESSION OF OSTEOPOROSIS AMONG POSTMENOPAUSAL WOMEN IN KARACHI, PAKISTAN - Sheikh Abdul Khaliq; Muhammad Saad; Namra Fatima et al. (Journal of University Medical & Dental College, 2017)
ABSTRACT: INTRODUCTION: Osteoporosis is a serious issue and fragility bone fracture in postmenopausal age is often the first sign. The limited availability of resources and aging population in developing countries causes the big challenge for osteoporosis. Even though disease can affect men and women of all races but Asian women especially older women who are post menopause are at highest risk. OBJECTIVE: The main objective and aim of prospective, analytical cross sectional study to evaluate the association and magnitude of risk factors in progression of osteoporotic fractures in women of Karachi those who crossed the age of menopause, these risk factors includes; lack of exercise, vitamin D deficiency, weight loss, advancing age, smoking and others. DURATION OF STUDY: The study was conducted during September 2015 - December 2015. SUBJECTS AND METHODS: Data has been collected from 100 postmenopausal women from different state owned hospitals. Data was analyzed through SPSS 19 by using logistic regression, Z-score and Test of proportion. RESULTS AND CONCLUSIONS: Among 100 participants, the mean age was 51 years (Age range was from 40-70 years). The results suggest that the most contributing and significant risk factors for Osteoporosis among postmenopausal women of Karachi are lack of exercise 89% (p< 0.05, significant as per t-Test), vitamin D deficiency 60% (p< 0.05, significant as per t-Test) and weight loss 58% (p< 0.05, significant as per t-Test). Logistic regression analysis determined that advancing age (p=0.008), family history of fracture (p=0.045), corticosteroids use (p=0.043) and eating disorder (p=0.03) are strongly related to Osteoporotic fracture.